ANALISIS DISIPLIN, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERATING - Amironah, Siti (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
The research aims to determine the relationship between work discipline, employee competence, motivation and employee performance with information technology variables as a moderating variable in employees of the Faculty of Education and Psycology, Yogyakarta State University. By knowing the magnitude of the influence of the variables studied, it is hoped that we can provide good recommendations to provide strategies for increasing employee loyalty to the organization. The method in this research uses the census method. This research is quantitative research, the sample in this research is 98 employees who work at the Faculty of Education and Psycology, Yogyakarta State University. The data collection technique was carried out using a questionnaire. The results of this research are, Work discipline has no effect on employee performance, Employee competency has an effect on employee performance, Work motivation has no effect on employee performance, Information technology is able to be a moderating variable between work discipline and employee performance, Information technology is able to be a moderating variable between competence employees on employee performance, information technology is not able to be a moderating variable between work motivation and employee performance.